Anticancer Effectivity of Nanocrystals Derived from Mangosteen (Garcinia mangostana) Peel Extract on Leukemia HL-60 Cells - Gondokesumo, Marisca Evalina; Novilla, Arina; Prahastuti, Sijani; Kusuma, Hanna Sari Widya; Widowati, Wahyu; Zahiroh, Fadhilah Haifa; Hadiprasetyo, Dhanar Septyawan; Surakusumah, Wahyu (Science and Technology Indonesia, 2025)
Leukemia, characterized by abnormal leukocyte proliferation, ranks ninth in Indonesia as the most common cancer. While treatments such as chemotherapy and radiation effectively target cancer cells, they also risk damaging healthy blood cells. This has spurred interest in exploring low-toxicity herbal compounds as potential therapies, with mangosteen peel emerging as a widely researched option. Nanotechnology, which has the potential to enhance the bioavailability of herbal compounds, is also a focus of extensive research. This study objective was to assess the impact of Mangosteen Peel Nanocrystal (MPN) on HL-60 leukemia cells by analyzing various parameters, including cytotoxicity, reactive oxygen species (ROS) levels, senescence, and gene expression changes. MPN was prepared with high-speed milling and characterized using particle size analyzers, microscopy, and stability assessments. HL-60 cells were cultured and subjected to MPN treatment. Cytotoxicity was evaluated using WST-8 assays, ROS levels were assessed using flow cytometry, and senescence analyses using Senescence-Associated b-Galactosidase Staining. AKT and FLT-1 gene expression were determined via qRT-PCR. MPN has been successfully characterized as a nanoparticle based on size, stability, and morphology. MPN has an impact on leukemia cells by increasing cytotoxicity, decreasing ROS levels, inducing senescence, and modulating AKT and FLT-1 gene expressions. The findings suggest potential implications for MPN in targeting leukemia cells. The study sheds light on the promising effects of MPN in leukemia cell models, indicating its potential applications in targeting cancer cells, inducing senescence, decreasing ROS levels, and modulating gene expressions related to cell survival and proliferation.